Assessing indigenous soil ureolytic bacteria as potential agents for soil stabilization - Aliyu, Abdulaziz Dardau; Mustafa, Muskhazli; Aziz, Nor Azwady Abd; Kong, Yap Chee; Hadi, Najaatu Shehu (Universitas Gadjah Mada, 2023)
Microbially induced carbonate precipitation by ureolysis is a biomineralization process that has been adapted by various microorganisms in different natural environments. This widespread natural phenomenon can be employed in numerous civil engineering and soil stabilization applications. In the present study, the potential of indigenous soil urease-producing bacteria as potential agents for soil stabilization method was investigated. Assessment of the eight active urease-producing bacterial species isolated from the farm soil samples has demonstrated that all the isolates were Gram-positive rod-shaped bacteria with promising characteristics such as the formation of endospore which is essential for bacterial survival in harsh conditions within the soil environment. The pH profile and growth profile of the isolates were studied and urease activity was measured by phenol hypochlorite assay method. Two isolates designated isolate O6w and isolate O3a were selected based on the highest urease activity recorded at 665 U/mL and 620 U/mL, respectively, and they were able to increase and sustain alkaline culture condition (pH 8.71 ± 0.01 and 8.55 ± 0.01) which was suitable for CaCO3 precipitation. The isolates were identified based on 16S ribosomal RNA sequencing to be Bacillus cereus (O6w) and Bacillus paramycoides (O3a). This current study suggested that indigenous soil ureolytic bacteria are potential raw material for the biotreatment of soils stability.